1966
DOI: 10.1097/00006842-196609000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the Ejaculatory Response in Men and Animals

Abstract: Observations and experiments relating to the causes and results of ejaculation in male mammals of several species reveal that in a number of different mammals, erection and emission can be mediated by purely spinal mechanisms. In intact males, emission is possible without genital stimulation, and the occurrence of emission is not automatically associated with orgasm in men or with the normal behavior sequelae to ejaculation produced in animals by copulation. These and other similarities between sexual reflexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
0
1

Year Published

1970
1970
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 27 publications
4
13
0
1
Order By: Relevance
“…This effect is hypothesized to result from failure of closure of the internal bladder sphincter (Shader, 1972), a necessary part of the sympathetically controlled series of smooth muscle contractions in emission. That loss of arousability is not apparently affected by these drugs in men-or in rats (Beach et al, 1966)-is consistent with the hypothesis of a separate, centripetal neural mechanism for this effect, which need not be disturbed simply because the path of semen expulsion has been misdirected by a peripheral mechanism. Beach et al (1966) related several such situations in men to observations of animals where seminal emission is separated from the behavioral sequelae of ejaculation.…”
Section: Hypothesis Of the Bipolar Origin Of Orgasmsupporting
confidence: 82%
See 1 more Smart Citation
“…This effect is hypothesized to result from failure of closure of the internal bladder sphincter (Shader, 1972), a necessary part of the sympathetically controlled series of smooth muscle contractions in emission. That loss of arousability is not apparently affected by these drugs in men-or in rats (Beach et al, 1966)-is consistent with the hypothesis of a separate, centripetal neural mechanism for this effect, which need not be disturbed simply because the path of semen expulsion has been misdirected by a peripheral mechanism. Beach et al (1966) related several such situations in men to observations of animals where seminal emission is separated from the behavioral sequelae of ejaculation.…”
Section: Hypothesis Of the Bipolar Origin Of Orgasmsupporting
confidence: 82%
“…That loss of arousability is not apparently affected by these drugs in men-or in rats (Beach et al, 1966)-is consistent with the hypothesis of a separate, centripetal neural mechanism for this effect, which need not be disturbed simply because the path of semen expulsion has been misdirected by a peripheral mechanism. Beach et al (1966) related several such situations in men to observations of animals where seminal emission is separated from the behavioral sequelae of ejaculation. They commented (p. 759) that "the simple discharge of seminal fluid does not, in and of itself, account for all of the behavioral changes which normally follow an ejaculation resulting from genital stimulation."…”
Section: Hypothesis Of the Bipolar Origin Of Orgasmsupporting
confidence: 82%
“…Spontaneous ejaculation, which is defined as the release of seminal fluids in the absence of apparent sexual stimulation, has been reported in several male land mammals, including Rodentia (rats [1], hamsters [2], guinea pigs [3], mice [4]), Cetartiodactyla (mountain sheep, warthogs (reviewed in [5]), tsessebes [6]), Carnivora (domestic cats [7], spotted hyenas (reviewed in [5])), Perissodactyla (horses [8]), and Primates (chimpanzees [9], (reviewed in [10]), humans (reviewed in [11])). Spontaneous ejaculation could possibly be widespread in various animals, including humans, but has passed unrecognized because it is an unpredictable and rare behavior that lasts only a few seconds, making it difficult to observe.…”
Section: Introductionmentioning
confidence: 99%
“…Three (not mutually exclusive) possible “functions” of animal spontaneous ejaculation have been discussed in previous publications: (1) a type of “masturbation” as a sexual outlet and/or for the removal of surplus (or abnormal) spermatozoa [5], [10], [12]–[16]; (2) an element of sexual display [6]; (3) no clear function, or misuse of inhibitory neural control system during drowsiness and sleep [8], [11], [17][20].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery that spontaneously emitted plugs could be recovered beneath wire-mesh cages if rats were muzzled or girdled led to much interest in the fate of such plugs. It was found that, unless restrained from doing so, male rats consume most spontaneously emitted plugs (Orbach, 1961;Beach, Westbrook, & Clemens, 1966;Orbach, Miller, Billimoria, & Solhkhah, 1967).…”
mentioning
confidence: 99%